A Wide Infected Radicular Cyst Invading Maxillary Sinus: Case Report - Esra Altunsoy; Tuğçe Çevik; Oğuzhan Görler (Cumhuriyet University, 2017)
Radicular cysts are among the most common lesions of the jaws. They develop around the apex of the devitalized root following pulp necrosis or trauma. Mostly radicular cysts are asymptomatic and small, they rarely reach large sizes. The purpose of this article is to present the enuclation of a radicular cyst case invading the maxillary sinus and reaching to orbital floor and the lateral nasal wall.